Pengaruh Return On Asset, Return On Equity, Net Profit Margin, dan Earning Per Share Terhadap Harga Saham - Wiyanto, Ersita Maharani; Muslimin, Muslimin (Gorontalo Accounting Journal, 2025)
This research aims to assess the influence of Return On Assets (ROA), Return On Equity (ROE), Net Profit Margin (NPM), and Earning Per Share (EPS) on the share prices of companies listed on the JII index. The approach used is a quantitative method. The population consists of 49 companies, with a sample of 13 companies selected using the purposive sampling method from 2021 to 2023. Secondary data was collected through data documentation. The results of hypothesis analysis with multiple linear regression using SPSS 27 show that ROA has a negative and significant influence on share prices, while ROE, NPM and EPS have a positive and significant influence on the share prices of companies listed on the JII index.